INVERTER DENGAN METODE KENDALI VARIABLE VOLTAGE VARIABLE FREQUENSI SEBAGAI PENGATUR KECEPATAN MOTOR INDUKSI 3 FASA - Emmanuel Agung Nugroho (Jurnal Elektra, 2019)
Induction motors cause inductive reactive power which results in a decrease in the power factor with high impedance. Another problem is the appearance of initial wear spikes caused by conventional motor starting systems. Conventional control systems lead to inefficient electricity consumption, inflexible production and damage to electric motors because they are always forced to work at maximum speed. Sinusoidal Pulse Width Modulation (SPWM) Inverters with the technique of controlling voltage and frequency simultaneously (Variable Voltage variable frequency) or also known as volt / hertz control can be a solution to the problem of improving power and power factor quality and at the same time able to control the motor at start or when the motor is running. This volt / hertz inverter is designed to generate a 3 phase voltage as a 3 phase AC motor controller from a 1 phase voltage source with a motor current in the form of a sine wave that is in phase against source voltage as evidence of a power factor improvement. In addition, electric motors can be controlled at speeds from a frequency of 10 Hz to 50 Hz linearly.